Strengthening the Shafi‘i Madhhab: Malay Kitab Jawi of Fiqh in the 19th Century - Yasrul Huda; Jajat Burhanuddin; Mahmood Kooria (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The supremacy of fiqh in Indonesian, and Southeast Asian, Islam has been widely acclaimed; the subject concerning the affairs of daily life, the core substance of fiqh, has its fertile grounds in Muslims religious ideas and practices. This article presents a historical analysis how the fiqh became popular in the region, which can be traced back to the 19th century. Taking Malay kitab jawi as the main subject of discussion, the shifting of religious concerns among the ‘ulamā’ (Muslim scholars) was of crucial significance. They increasingly engaged in dealing with the Muslims’ need of guidance in primarily prescriptions for worship (‘ubūdiyah). This study traces the historical aspect in the spread of the Shafii school, along with the development of the Malay textual tradition. As a result, kitab jawi on fiqh by Southeast Asian ‘ulamā’ grew considerably, in both number and religious authority, in line with the rise of learning institutions (pondok), leading the subject to appear as religiously essential to be produced, and reproduced, to become an established school for Muslims of the region.